Does financial openness promote economic integration? Some evidence from Europe and the CIS - Fabrizio Carmignani; Abdur R. Chowdhury (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
We study whether financial openness facilitates the economic integration of formerly centrally planned economies with the EU-15. Two dimensions of economic integration are considered: cross-country convergence of per-capita incomes and bilateral trade in goods and services. We find that more financially open economies effectively catch-up faster and trade more with the EU-15. These integration-enhancing effects occur over and above any effect stemming from domestic financial deepening and other factors determining growth and trade.
Keywords: F10; F15; F30; F36; F40; 330; economic integration; financial openness; gravity models; catching-up; Kapitalmarktliberalisierung; EU-Staaten; GUS-Staaten